Criminal law, ageism and dependency. Are the events that occurred in nursing homes during the COVID-19 pandemic punishable? - Hava García, Esther (EUNOMÍA. Revista en Cultura de la Legalidad, 2022)
The present work aims to provide the necessary theoretical support to determine whether it is possible to subsume some of the events that occurred in nursing homes during the first wave of the COVID-19 pandemic under the criminal types of reckless homicide and refusal to provide health care. This will be done through an analysis of the data that today can be considered less controversial and taking into account the few pronouncements made in this regard by the court decisions that have been issued so far on said events. Naturally, the objective is not to advocate for the initiation of prospective proceedings but, rather, to elucidate whether there is sufficient evidence to defend the posture that some of those events may have been criminal in nature.
Keywords: Criminal Law; ageism; dependency; COVID-19; reckless homicide; refusal to provide health care